2017
DOI: 10.18488/journal.aefr.2017.76.573.588
|View full text |Cite
|
Sign up to set email alerts
|

Education, Employment and Gender Gap in Mena Region

Abstract: Article HistoryEducation is central to human capital capacity-building, and major determinant of economic development, as it has long been considered as an important investment both for social and economic development. The Middle East and North African countries have been aware of the importance of education therefore considered it as a key part of their strategies and future planning; enrollments at different levels of education have improved dramatically over the past few decades. This study is an empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…According to the study participants, the question of whether to migrate was most often decided by the male head of the household (61.0%), versus decisions made jointly by family members (39.0%) (Table 2). This nding is consistent with the literature, where previous studies have reported signi cant gender gaps in MENA countries with respect to autonomy and decision-making [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…According to the study participants, the question of whether to migrate was most often decided by the male head of the household (61.0%), versus decisions made jointly by family members (39.0%) (Table 2). This nding is consistent with the literature, where previous studies have reported signi cant gender gaps in MENA countries with respect to autonomy and decision-making [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…The gender gap is a pressing issue globally, and it is set as the fifth key goal in the United Nations SDGs [8]. Accordingly, such a topic has been addressed in earlier studies focusing on Jordan or the MENA region, where several socioeconomic and cultural factors were attributed [3,13]. According to a report by PriceWaterhouseCoopers (PWC) [9], the increased participation of women in employment can result in GDP increases of around 57%.…”
Section: Pillars Of Gender Equality In Stemmentioning
confidence: 99%
“…It is widely acknowledged globally that women are not still on par with men in terms of economic opportunities [2] despite enjoying greater educational advancements. This concern is receiving increasing global attention, where studies have shown that the empowerment of women results in better social cohesion and as such, plays an important role in economic development and growth [3], pushing forward the agenda for sustainable development [4,5]. This is particularly evident in the area of STEM, where the inclusion of men and women in a collaborative working relationship promises more elevated levels of innovation and productivity within such an evolving domain [1].…”
Section: Introductionmentioning
confidence: 99%
“…Families and individuals invest in education in the hopes of benefiting from betterwork opportunities in the labor market, but in MENA (except the oil producer countries) such returnsfrom the labor market are among the lowest in the world (Patrinos, 2016).Some of the achievements over the last fiftyyears have beenthe significant investments in the sphere of Education reaching 4.5% of their national income on an average and a greater degree of gender parity (Dandan & Marques, 2017;Psacharopoulos & Patrinos, 2018). It is pertinent to mention here thatthe lower and middle income countries allocate, on an average, 4.5% of their GDP and 15.2% of their total public spending to education, as seen in figure 2 (Galal & Kanaan, 2010).…”
Section: Stakeholders Of Educationmentioning
confidence: 99%